Comparison of Percutaneous Dilatational Tracheostomy Guided by Ultrasound and Bronchoscopy in Critically Ill Obese Patients. (19th October 2017) - Song, Jieqiong; Xuan, Lizhen; Wu, Wei; Zhu, Duming; Zheng, Yijun
Abstract : Objectives: This study aimed to compare the efficacy and safety of percutaneous dilatational tracheostomy (PDT) with ultrasound (US) or bronchoscopic guidance for critically ill patients, notably obese patients. Methods: This work was a retrospective study. The study included mechanically ventilated patients who underwent PDT from August 2013 to July 2015 in the Department of Critical Care Medicine of Zhongshan Hospital. The patients were classified according to the different guidance methods during tracheotomy and their body mass index in the following 4 groups: normal bronchoscopy group, normal US group, obese bronchoscopy group, and obese US group. The parameters, including operation time, number of punctures, intraoperative and postoperative complications, duration of the intensive care unit stay, hospitalization time, and mortality, were recorded and compared between groups. Results: Compared with the obese bronchoscopy group, the obese US group had a significantly shorter PDT operation time (mean ± SD, 12.8 ± 4.8 versus 16.2 ± 4.4 minutes; P = .026), fewer punctures ( P = .011), and a lesser amount of intraoperative hemorrhage (12.1 ± 4.6 versus 16.8 ± 4.3 mL; P = .009). There were no significant differences in these parameters between the normal US and normal bronchoscopy groups. Conclusions: Ultrasound‐guided PDT significantly reduced the number of punctures and the operation time compared with bronchoscopy‐guided PDT, and it decreased intraoperative hemorrhage in critically ill obese patients. Percutaneous dilatational tracheostomy with US guidance was a faster, safer, and more accurate method of airway management.